1999
DOI: 10.1177/019262339902700510
|View full text |Cite
|
Sign up to set email alerts
|

Prompt Recovery of Damaged Adrenal Medullae Induced by Salinomycin

Abstract: The morphologic changes in the adrenal medullae of rats treated with an ionophore antibiotic, salinomycin, are described. Male rats of approximately 7 wk of age were treated orally with a single dose of salinomycin at 80 mg/kg body weight. Following this treatment, the adrenal glands were examined, using immunohistochemistry, for neurofilament, laminin, fibronectin, and S-100 protein; the glands were also examined using transmission electron microscopy. One hour after the treatment, a karyopyknosis was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
4
7
0
Order By: Relevance
“…After treatment with 10 µM monensin for 30 min, GNOM-GFP-labeled compartments and ST-mRFP-labeled Golgi apparatus were strongly enlarged and were also colocalized ( Figure 3G; Supplemental Figures 4G to 4I). Similar results ( Figure 3H; Supplemental Figures 4J to 4L) were obtained when we applied 10 µM salinomycin for 30 min, a monovalent cation ionophore that is assumed to function similarly to monensin (Chen-Pan et al, 1999). We also confirmed that the Golgi marker, ST-mRFP, behaves in a similar manner to GNOM-GFP after treatment with the Wm and ConcA (Supplemental Figures 5A to 5C).…”
Section: Gnom-gfp Localizes To the St-mrfp-labeled Organellessupporting
confidence: 84%
“…After treatment with 10 µM monensin for 30 min, GNOM-GFP-labeled compartments and ST-mRFP-labeled Golgi apparatus were strongly enlarged and were also colocalized ( Figure 3G; Supplemental Figures 4G to 4I). Similar results ( Figure 3H; Supplemental Figures 4J to 4L) were obtained when we applied 10 µM salinomycin for 30 min, a monovalent cation ionophore that is assumed to function similarly to monensin (Chen-Pan et al, 1999). We also confirmed that the Golgi marker, ST-mRFP, behaves in a similar manner to GNOM-GFP after treatment with the Wm and ConcA (Supplemental Figures 5A to 5C).…”
Section: Gnom-gfp Localizes To the St-mrfp-labeled Organellessupporting
confidence: 84%
“…The Schwann cells were closely associated with nerve bers (Figure 5a, b, d). Other features were similar to those previously described (1).…”
Section: Transmission Electron Microscopysupporting
confidence: 86%
“…Undifferentiated chromaf n cells, previously called pheochromoblasts became apparent 10 hours after administration of salinomycin/kg 80 mg of body weight, with electron dense cytoplasm due to the presence of numerous free ribosomes and catecholamine granules less than 80 nm in diameter. After 17 hours, only differentiated chromaf n cells were observed, with full morphological recovery at 24 hours (1).…”
Section: Introductionmentioning
confidence: 99%
“…Because we never observed differentiated chromaffin cells in mitosis, we can hypothesize that the increase in number of these cells during development is due to a proliferation of undifferentiated precursors present in the kidney. Chen-Pan et al (1999) in fact demonstrated that in rat adrenal medulla damaged by salinomycin, new chromaffin cells differentiate from unrecognized precursors present in the medullary tissue.…”
Section: Discussionmentioning
confidence: 91%